APLIKASI TIKTOK SEBAGAI MEDIA DAKWAH MAHASISWA PRODI KPI FAKULTAS DAKWAH IAIDA DI MASA PANDEMI COVID 19 - Agung Obianto (JDARISCOMB:Jurnal Komunikasi dan Penyiaran Islam, 2023)
With the development of technology in communication, it is easier to convey information from one place to another, in various parts of the world. Da'wah is an activity that calls for and invites people to obey Allah. Fardiyah da'wah is an invitation or call to the path of Allah SWT which is carried out by a da'i (caller) to other people individually with the aim of moving al mad'u to a better condition and pleasing Allah SWT. The reciprocal relationship between life in this world and the mass media has been going on for a long time. The development of technology in communication in the world is getting faster and more advanced, including the emergence of tick tock. Because at this time people negatively evaluate the tik tok application, even though we can take positive values in it, depending on how we digest it. We know what's interesting in this tiktok application, during the current pandemic, many students use the tiktok application as a form of outlet for social media activities and da'wah, proving that we can bring tik tok to the path of da'wah as well.